1999
DOI: 10.1007/s002200050701
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of the Small Quantum Cohomology Rings of Projective Hypersurfaces

Abstract: We give an explicit procedure which computes for degree d ≤ 3 the correlation functions of topological sigma model (A-model) on a projective Fano hypersurface X as homogeneous polynomials of degree d in the correlation functions of degree 1 (number of lines). We extend this formalism to the case of Calabi-Yau hypersurfaces and explain how the polynomial property is preserved. Our key tool is the construction of universal recursive formulas which express the structural constants of the quantum cohomology ring o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Let us summarize the results of [3]. In [3], we showed that the structure constants L N,k,d m of QH * e (M k N ), (N − k ≥ 2), can be obtained by applying the recursive formulas in Appendix B,…”
Section: Review Of Results For Fano and Calabi-yau Hypersurfaces And mentioning
confidence: 99%
“…Let us summarize the results of [3]. In [3], we showed that the structure constants L N,k,d m of QH * e (M k N ), (N − k ≥ 2), can be obtained by applying the recursive formulas in Appendix B,…”
Section: Review Of Results For Fano and Calabi-yau Hypersurfaces And mentioning
confidence: 99%
“…In [4], we have constructed the recursive formulas that describe the rational structural constant L N,k,d n of the quantum Kähler sub-ring of M k N , which is the degree k hypersurfaces in CP N −1 , in terms of those of M k N +1 when the degree of the rational curves concerned is no more than 5. These recursive formulas determine the structural constants of the quantum cohomology ring of M k N with the aid of the initial conditions given by the following formula in [5]: (jw + (k − j)), (1.1) where N − k must be greater than 1.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…These recursive formulas determine the structural constants of the quantum cohomology ring of M k N with the aid of the initial conditions given by the following formula in [5]: (jw + (k − j)), (1.1) where N − k must be greater than 1. But in [4], our construction of the recursive formula needs some explicit data of the structural constants coming from the higher degree curves, and the determination of the recursive formulas gets extremely harder as the degree of the rational curves grows.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…On the other hand, we conjectured the recursive formulas that evaluate the structure constants of the quantum Kähler sub-ring of M k N in terms of the ones of M k N +1 when N −k ≥ 2 [5], [11]. These recursive formula is strong enough to determine all the structure constants of M k N in this region.…”
Section: Introductionmentioning
confidence: 94%
“…To clarify the meaning of the virtual structure constants introduced in [5], we had better introduce the B-model deformation parameter x instead of t and consider the following Gauss-Manin system. We can derive the following equality from the above equations:…”
Section: N − K = 1 Casementioning
confidence: 99%